Evolução molecular dos receptores da oxitocina e da vasopressina em animais domesticados e de interesse comercial - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Oxytocin and vasopressin are closely related nonapeptides that arose from tandem duplication occurred in the common ancestor of jawed vertebrates and play important physiological and behavioral functions in many organisms. Its activities are mediated through interactions with the oxytocin receptor (OXTR) and vasopressin receptors (AVPR1a, AVPR1b and AVPR2). The aim of this study is to characterize the molecular evolution of this family of receptors in a large set of organisms. As well as, assess the genetic variability of the OXTR from Ovis aries species that does not have its genome available in databases. Due to the conservation of nonapeptides, at least considering the mammals, it is believed that the evolution of the system is going through their receptors, which therefore are the focus of this study. Through nucleotide and protein sequences for all oxytocin and vasopressin receptors obtained in databases UniProt and HMMER, phylogenetic analyzes were performed by maximum likelihood in the Mega 5.0 program. Available data on the website Genomicus were used to carry out the synteny and neighborhood. The pattern of molecular evolution was established using a set of 23 mammalian species using the Paml 4.6 package. To contribute to the knowledge of the Ovis aries species it was analyzed the OXTR gene, in the Creole Lanada breed (N = 35) that presents a distinct pattern of selection compared to the breeds Ile de France (N = 6) and Ideal (N = 5) that are selected for cutting and wool. Our results indicate that OXTR, AVPR1A, AVPR1b, AVPR2 and the sintenic block of these receptors emerged with the common ancestor of vertebrates in the first genome duplication event. First, was originated the ancestral gene of AVPR1A and AVPR1b and the ancestral gene of OXTR and AVPR2. The four receptors observed today originated after the second genome duplication event occurred in the common ancestor of vertebrates. In terms of molecular evolution were found distinct patterns between domesticated and wild animals in the AVPR1A and AVPR1b receptors. This indicates that domesticated animals are under positive selection for these genes, clearly molecular mark which may be linked to the process of selection for docility, in the context of convergent evolution. For the Ovis aries species was amplified a total of 1644 base pairs (bp) of DNA obtained from three sheep breeds studied. Although has been found variation between the breeds, there is no break in the pattern of neutrality with signal of purifying selection. This strengthens the idea that the whole system is evolvingthrough the two AVP receptors, whose phylogenetic origin is common, AVPR1A and VPR1b.
Molecular evolution of oxytocin and vasopressin receptors in domesticated animals of commercial interest
Keywords: Evolução molecular; OXTR; Ovelhas; Mamíferos; Domesticação; Molecular evolution; Sheep; Mammals; Domestication